Bioconversion of Industrial Cassava Solid Waste (Onggok) to Bioethanol Using a Saccharification and Fermentation process - Soeprijanto, Soeprijanto; Qomariyah, Lailatul; Hamzah, Afan; Altway, Saidah (International Journal of Renewable Energy Development, 2022)
Cassava solid waste (Onggok) is a by-product of the starch industry containing a lot of fiber, especially cellulose and hemicellulose. It has the potential to be converted to bioethanol. This work aimed to evaluate the effect of feedstocks ratio for the optimal bioethanol production via enzymatic and acidic hydrolysis process in a batch fermentation process. The effect of alpha-amylase and glucoamylase activities was studied. The sulfuric acid concentrations in the hydrolysis process in converting cassava into reducing sugar were also investigated. The reducing sugar was then fermented to produce ethanol. Enzymatic and chemical hydrolysis was carried out with the ratio of onggok(g)/water(L), 50/1, 75/1, and 100/1 (w/v). In the enzymatic hydrolysis, 22.5, 45, and 67.5 KNU (Kilo Novo alpha-amylase Unit) for liquefaction; and 65, 130, and 195 GAU (Glucoamylase Unit) for saccharification, respectively of enzymes were applied. The liquefaction was carried out at 90-100â°C for 2 hours. The saccharification was executed at 65 â°C for 4 hours. Meanwhile, the acidic hydrolysis operating condition was at 90-100 â°C for 3 hours. The fermentation was performed at pH 4.5 for 3 days. Fourier Transform Infra-Red (FTIR) analysis was conducted to evaluate the hydrolysis process. The highest ethanol was yielded in the fermentation at 8.89% with the ratio of onggok to water 100:1, 67.5 KNU of alpha-amylase, and 195 GAU of glucoamylase. Ethanol was further purified utilizing fractional distillation. The final ethanol concentration was at 93-94%.